Shay Trettin: capstone - Trettin, Shay, artist (Colorado State University. Libraries, 2019)
The artist's statement: My artwork is a combination of mediums: printmaking, illustration, traditional drawing, sculpting, and textile arts. Using these different mediums my work confronts the subject matters of our natural world: nature, life, and death are the three main subjects I explore through my art. I like to play with our society's morbid concepts of these topics. Death is a part of life, and to come to terms with that is the first step to truly being alive. Skulls, bones, and plants are common motifs throughout my works. All these subject matters are intricately related to one another and through my art I try to create a conversation between them. Over my lifetime I have acquired many plush pillows. I have always been intrigued by the simplicity of some, and the complexity of others. The stitch patterns, the softness of the material, the firmness of the filling. All these things were, and still are, something I wanted to understand at a level more than just studying them. I enjoy the idea of a large-scale version of these plants. While keeping a fun and soft demeanor, I wanted to bring the rawness into play by using hand stitching methods and veering away from a sewing machine. Historically weavings and tapestries are used to memorialize or commemorate, and I felt that this would tie well together with my plushes and the route I've found myself on with my current works. Within my weavings I found solace in the complex patterns and repetition, often getting lost in myself without getting lost in my thoughts. In the spring of 2019 I tried my hand at a double weave pickup. Being face to face with death on many occasions through different experiences I bring out my longing for life throughout my work. I try to create a playful, yet serious, dialogue about mortality within my creations. Death is a loss of life, and to me that can come in many forms. From the death of a loved one to the death of a past self and past ideals, no one can escape death. "I do not fear death. I had been dead for billions and billions of years before I was born and had not suffered the slightest inconvenience from it."-Mark Twain.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers